Research on the reconstruction configuration and motion behavior of unmanned metamorphic vehicle. (15th February 2022) - Liu, Jun; Yang, Pengliang; Lu, Mingming; Sun, Lei; Huang, He
As a new type of ground transportation system, an unmanned metamorphic vehicle can naturally switch between wheeled driving and legged walking through vehicle reconstruction. Therefore, compared with traditional vehicles, unmanned metamorphic vehicles can move quickly on structural roads and have high trafficability on nonstructural roads. Furthermore, an unmanned metamorphic vehicle is applicable to interstellar detection and earthquake rescue. In this study, the topological structure of an unmanned metamorphic vehicle was designed and the reconstruction process was described. In addition, a kinematic analysis was conducted on the three stages (supporting, lifting, and standing-up) of reconfiguring the metamorphic vehicle. The kinematic and corresponding dynamic models were established based on the screw theory and the Lagrange equation. A Matlab/Simulink simulation was then carried out for the unmanned metamorphic vehicle. The simulation results describe the motion behavior of the system reconstruction, illustrating that the established kinematic and dynamic models are reasonable. Finally, the correctness of the abovementioned kinematic and dynamic models was further verified by Adams virtual prototype simulation. The above findings provide a solid foundation for future studies on stability control during the reconstruction of unmanned metamorphic vehicles.